Prophylactic Placement of an Inferior Vena Cava Filter During Aspiration Thrombectomy for Acute Deep Venous Thrombosis of the Lower Extremity. (May 2016) - Kwon, Se Hwan; Park, So Hyun; Oh, Joo Hyeong; Song, Myung Gyu; Seo, Tae-Seok
Purpose: To evaluate the effect of an inferior vena cava (IVC) filter during aspiration thrombectomy for acute deep vein thrombosis (DVT) in the lower extremity. Materials and Methods: From July 2004 to December 2013, a retrospective analysis of 106 patients with acute DVT was performed. All patients received an IVC filter and were treated initially with aspiration thrombectomy. Among the 106 patients, DVT extension into the IVC was noted in 27 but was not evident in 79. We evaluated the presence of trapped thrombi in the filters after the procedure. The sizes of the trapped thrombi were classified into 2 grades based on the ratio of the maximum transverse length of the trapped thrombus to the diameter of the IVC (Grades I [≤ 50%] and II [> 50%]). Results: A trapped thrombus in the filter was detected in 46 (43%) of 106 patients on final venograms. The sizes of the trapped thrombi were grade I in 12 (26.1%) patients and grade II in 34 (73.9%). Among the 27 patients with DVT extension into the IVC, 20 (74.1%) showed a trapped thrombus in the filter, 75% (15 of 20) of which were grade II. Among the 79 patients without DVT extension into the IVC, 26 (32.9%) showed a trapped thrombus in the IVC filter, 73% (19 of 26) of which were grade II. Conclusions: Thrombus migration occurred frequently during aspiration thrombectomy of patients with acute DVT in the lower extremity. However, further studies are needed to establish a standard protocol for the prophylactic placement of an IVC filter during aspiration thrombectomy.